1991
DOI: 10.1007/bf01464288
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical waste water treatment using high overvoltage anodes Part II: Anode performance and applications

Abstract: The performance of highly doped SnO2 anodes for the oxidative treatment of biologically refi'actory waste water was compared with PbO2 and Pt. The oxidation of a wide range of organic compounds proceeds with an efficiency which is about 5 times higher than with platinum anodes. The oxidation efficiency was found to be independent of the pH of the wa_ter. In chloride containing media, SnO2 anodes produce less chlorine gas than platinum anodes and hence show less potential to form hazardous chlorinated organic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
191
1
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(200 citation statements)
references
References 4 publications
3
191
1
5
Order By: Relevance
“…4b) and was attributed to a low oxygen evolution overvoltage [35][36]. Efficiency of Ti/Ta2O5-SnO2 electrodes 221 in regards of MB oxidation was confirmed by the data on COD and NPOC removal (Fig.…”
supporting
confidence: 52%
“…4b) and was attributed to a low oxygen evolution overvoltage [35][36]. Efficiency of Ti/Ta2O5-SnO2 electrodes 221 in regards of MB oxidation was confirmed by the data on COD and NPOC removal (Fig.…”
supporting
confidence: 52%
“…Electrochemical techniques which allow reduction of the quantity of organic pollutants in solution are: (a) Separation by electrofloculation [2], (b) Oxidation by electrogenerated Fenton's reagent [3,4], (c) Direct oxidation on a suitable anode material [5][6][7][8][9], where organic molecules are degraded into smaller molecules by successive oxygen atom transfer until complete destruction of the carbon skeleton [10]. The complete oxidation of phenol in aqueous solution by electrochemical means has been carried out on anode materials such as SnO 2 [7,8], PbO 2 [6,11,12], WO 3 [13] and BDD [14,15]. Stucki et al showed that a SnO 2 anode gives better results than PbO 2 in COD abatement for phenol solutions [7].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the use of electrochemical oxidation methods results in a 38% and 90% TOC removal when platinum and doped SnO 2 are employed, respectively [3±8]. KoÈ tz et al [5,6] were the pioneers in the study of physical and electrochemical properties of doped SnO 2 anodes. These electrodes present a low resistivity, high chlorine and oxygen evolution overpotentials, a high exchange current density for the Ce 3+ ® Ce 4+ reaction and an e ciency and a rate of phenol removal much higher than for Pt and PbO 2 .…”
Section: Introductionmentioning
confidence: 99%